Sintesis Keterampilan Guru Mengajar Literasi Sains Melalui Keterampilan Berpikir Tingkat Tinggi - Rabiudin Rabiudin (Jurnal Inovasi Pendidikan dan Sains, 2023)
The objective of this study is to measure teachers' skills in teaching scientific literacy based on High Order Thinking Skills (HOTS). These teaching skills are seen from the planning of learning, preparation of learning media, teaching skills, mastery of teaching materials, and skills for conducting evaluations according to the level of literacy students need intervention, basic, capable, skilled, and need creative space. This study uses an explorative descriptive qualitative method with data collection techniques using observation and in-depth interviews. The sample for this study consisted of 25 teachers at Islamic elementary schools (MI) in Sorong City and Sorong Regency, West Papua. Important research findings show that most teachers are skilled in teaching HOTS-based science literacy at the literacy level need intervention and at the basic level or cognitive level of remembering and understanding but have difficulty teaching at the skillful literacy level and need space for the creation or difficulty teaching at the evaluation and creation level on cognitive review.